Influencia de las características del empleo formal en el sector privado de la región Loreto, durante el periodo 2013 – 2022 - Cornelio Chujutalli, Jessika Edith (2025)
This research analyzed the characteristics of formal employment in the private sector of Loreto (2013-2022) to identify its relationship with gender, age, and company size, using a non-experimental quantitative approach with data from the Central Reserve Bank, Ministry of Labor, and INEI. Through Pearson correlation and regression analysis (R²), it was determined that: 1) The female gender showed a highly significant influence (R²=77.16%), being key in the composition of formal employment— a novel finding that contrasts with previous studies focused on income or education; 2) The 30-44 age group had the strongest correlation (r=0.90; R²=81.47%), establishing itself as the main contributor, supporting the Keynesian theory of labor stability productivity; and 3) Small businesses (2-10 workers) had the highest correlation (r=0.62), generating between 51.31% and 68.42% of formal employment, challenging the narrative that prioritizes large enterprises. Large companies (>100 workers) showed a marginal impact (R²=4.48%). It is concluded that formal employment in Loreto is structured by gender dynamics, age-related productive cycles, and small-scale business models, with implications for public policies focused on formalizing micro and small enterprises (MSEs), closing generational gaps, and promoting gender equity. Limitations include reliance on secondary data and the omission of educational variables. This study provides empirical evidence to rethink development strategies in Amazonian regional economies, highlighting the need for intersectional approaches in labor formalization.